COMMUNICATION INTERPERSONAL BETWEEN PEOPLE OLD WITH CHILD TEENAGE SMOKER ACTIVE: Education Descriptive Qualitative Bandar Setia Village, Kec. Percut Sei Tuan Kab. Deli Serdang - Dea Amelia Rahmawati; Muhammad Alfikri (KABILAH : Journal of Social Community, 2022)
Abstract: This study examines the interpersonal interaction of parents and adolescents who are active smokers in the village of Bandar Setia, sub-district. Percut Sei Tua, Kab. serdang deli. This study aims to find out how the interpersonal interactions of parents and adolescents are active smokers and what are the supporting factors, barriers between parents and adolescent smokers in the village of Bandar Setia. The research location is located in the village of Bandar Setia. In this study, information was obtained from 16 informants, namely 8 parents and 8 teenagers. The data collection technique is to collect information in the field using observation, interview and documentation techniques. The research used a qualitative descriptive method which was carried out in the village of Bandar Setia. Communication by parents and children is closer, there is a sense of empathy, support, positive feelings, and equality, and parents pay attention to their children who smoke. Factors that support communication between parents and children of smokers are closeness within a family and mutual support for one another, meanwhile, work and the lack of attention of parents towards children are factors that hinder communication. The impact of teenage smoking on health, social and psychological and financial problems. Keywords: Interpersonal Communication, Parents, Adolescents, Active Smokers